Health risks assessment diagnosis of toxic chemicals (heavy metals) via food crops consumption irrigated with wastewater - Khan, Muhammad Abrar; Mehmood, Sultan; Ullah, Faizan; Khattak, Adnan; Zeb, Muhammad Alam (Penerbit Universiti Kebangsaan Malaysia, 2017)
The present study investigated the concentration of metals in commonly grown vegetables (Luffa acutangula L., Zea mays L., Solanum melongena L.) irrigated with waste water in District Bannu, Khyber Pakhtunkhwa, Pakistan. The pH (5.80) and electrical conductivity (13 dS/m) of waste water indicated the acidic nature that is not suitable for irrigation purposes. Soil and vegetables samples were analyzed for metals concentration through flame atomic absorption spectrometry (Varian FAAS-240). The findings showed that waste water irrigated soil was highly contaminated with Cd (4.62 mg/kg) which was above permissible limits set by European Union Standard (EU 2006, 2002). The concentrations of heavy metals such as Cr and Cd in vegetables were higher than the permissible limits set by World Health Organization/Food and Agriculture Organization U.S.A guidelines 2001. The health hazard quotient (HQ) of waste water irrigated vegetables was observed higher for Ni (0.699-0.1029 mg/kg), (0.0456-0.1040 mg/kg), (0.731-0.0994 mg/kg) in Luffa acutangula, Solanum melongena and Zea mays, respectively. The study concluded that the consumption of commonly grown vegetables in waste water zone of the study area may pose potential health threats in local population.